2009
DOI: 10.1038/cdd.2009.72
|View full text |Cite
|
Sign up to set email alerts
|

p57Kip2 is a repressor of Mash1 activity and neuronal differentiation in neural stem cells

Abstract: Mammalian central nervous system (CNS) development is a highly organized process involving the precise and coordinated timing of cell-cycle exit, differentiation, survival, and migration. These events require proper expression of pro-neuronal genes but also repression of alternative cell fates and restriction of cell-type-specific gene expression. Here, we show that the cyclindependent kinase (CDK) inhibitor p57Kip2 interacted with pro-neuronal basic helix-loop-helix (bHLH) factors such as Mash1, NeuroD, and N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(39 citation statements)
references
References 39 publications
1
38
0
Order By: Relevance
“…Kip2 is a multifunctional protein (Joseph et al, 2003(Joseph et al, , 2009Vlachos et al, 2007). Altogether, these results demonstrated that the presence of p57…”
Section: Kip1supporting
confidence: 60%
See 2 more Smart Citations
“…Kip2 is a multifunctional protein (Joseph et al, 2003(Joseph et al, , 2009Vlachos et al, 2007). Altogether, these results demonstrated that the presence of p57…”
Section: Kip1supporting
confidence: 60%
“…, most probably because of its Cdk inhibitory function, is frequently considered as a nuclear protein; however, cytoplasmic expression of this protein has been demonstrated in various tissue, tumors and derived cell lines (www.proteinatlas.org; Barbe et al, 2008;Nan et al, 2005;Matsumoto et al, 2000;Pateras et al, 2006;Bozdogan et al, 2008;Joseph et al, 2009). In fact, as for the other members of the family, p21…”
Section: Kip2mentioning
confidence: 99%
See 1 more Smart Citation
“…The observation that glial cell derivatives were not preferentially surviving or proliferating at higher rates in response to p57kip2 knockdown indicates that p57kip2 is an intrinsic adult neural stem cell regulator and that it plays a role in glial fate decision. During development, p57kip2 was shown to inhibit Mash1 (Ascl1) expression and to prevent neuronal differentiation of embryonal neural stem and progenitor cells (Joseph et al, 2009). No overlap of p57kip2 and neuronal markers such as NeuN was detected in our SGZ sections.…”
Section: Research Articlementioning
confidence: 89%
“…The N-terminal domain of p57 Kip2 is also the site of interaction with MyoD and other basic helix-loop-helix (b-HLH) transcription factors, such as Mash1, NeuroD, and Nex/Math2 (35)(36)(37)(38)(39). p57 Kip2 has also been reported to interact with Nuclear Receptor Related 1 (NURR1) protein.…”
Section: P57 Kip2 Proteinmentioning
confidence: 99%